INTEGRATION OF REMOTE SENSING AND GEOPHYSICAL METHODS FOR STRUCTURAL AND LITHOLOGICAL MAPPING IN A PART OF PRECAMBRIAN BASEMENT ROCKS, NORTHERN NIGERIA - Olatunji, S (university of eloued -جامعة الوادي, 2022)
Landsat 8 OLIdata, Aeromagnetic data,and Radial Vertical Electrical Sounding (RVES) survey data were integrated to map lithology, delineate structures and their trends, and delineate possible mineralized zones in the area. Landsat 8 OLI data yielded a colorcomposite image, and surface lineaments map of the area. The aeromagnetic maps were utilized to map lithology, and subsurface structures. A radial survey confirmed the fractures derived from the structural maps. Results classified the area into three geological units viz: migmatite, banded gneiss, and quartzite. The banded gneiss is the most deformed and contains series of structures that are significant for mineral and groundwater explorations. Clay alteration is the most dominant in the area, followed by iron oxide alterations. Lineament alignments are N-S, NNW-SSE, NNE-SSW, NE-SW,and E-W directions
article
Keywords: Landsat 8 OLI,Aeromagnetic, Remote sensing, Radial Sounding, Lineament